Vermicomposta como alternativa organica en la produccion de tomate en invernadero - Rodriguez Dimas, N.=700 1 Cano Rios, P.; Favela Chavez, E.; Figueroa Viramontes, U.; De Paul Alvarez, V.
(En, Es)
Ilus., 46 ref.
Keywords: LYCOPERSICON ESCULENTUM; ABONOS ORGANICOS; HUMUS; OLIGOCHAETA; CULTIVO PROTEGIDO; NUTRIENTES; MEXICO